Avaliação dos pés de diabéticos atendidos em um serviço de referência localizado em Fortaleza-CE - Nascimento, Luciana Maria de Oliveira (2002)
The current study aimed to check the frequency of the foot in risk, in diabetic patients. The sample was of 250 patients who are assisted in the Clinic of Endocrinoiogy and Diabetes of HUWC, between may/2000 and dec./2001. The patients were evaluated through physical, neurological and vascular examinations. According to the results, most of the subjects were female (84%), with 18 to 60 years of age (55%); 40% referred having the disease for more than 10 years and 66% confírmed not practicing any kind of physical exercise. In the overall sample, 81% presented some kind of deformity, calluses and físsures, either in one of the feet or in both. In the neurological examination, 24% had tactile sensibility and temperature involved; 20% also had vibratory sensíbility involved and, in 11%, the Achilles reflex was absent. In the vascular examination, it was observed that 3% had absent dorsal foot pulse beat and 7% also had absent posterior tibial pulse beat. The physical alterations were greater than the neurological and vascular ones, and the last ones were smaller than the neurological alterations. No statistically signifícant relation was found between the neurological, physical and vascular examinations and the variable sex. It was signifícant, however, the relation between age and tactile sensibility (p = 0.040), Achhilles reflex (p = 0.020) and posterior tibial pulse beat (p= 0.007). It was also signifícant the relation between Achilles reflex and the variables time with the disease time (p = 0.000) and physical activity (p = 0.040). It was concluded that 95% of the subjects showed at least one of the clinicai signs which are suggestive of foot in risk. The results also idicated that the ones involved are not taking adequate care of their feet. Such findings represent an alert, especially for the nurses, who are responsible for the education in diabetes, thus becoming essencial the detection of the foot in risk.